A Comparison Between 10-Day and 12-Day Concomitant Regimens for Helicobacter Pylori Eradication - Rubina Shah, Tariq Tahir Butt, Bushra Gohar Shah (Pakistan Journal of Medical & Health Sciences, 2022)
pylori (Helicobacter pylori) is the most prevalent infection worldwide which leads to gastric ulcer and cancer. In our research work, patients infected with H. pylori were given concomitant treatment for 10 and 12 days and compared to find the efficiency of treatment. Objective: The objective of this study is to find a cost-effective therapeutic method for the treatment of H. pylori. Previous 14-day treatment was effective but it was expensive due to the high cost of antibiotics as well as the negative side effects of the treatment, so an alternative method is required to reduce the need of costly antibiotics and the duration of treatment. Study design: It is a comparative study with statistical approach, conducted in the medicine department of Sialkot Medical College, Sialkot for the duration of six months from June 2021 to November 2021. Methods: For this study, 196 patients with gastric ulcers were selected and confirmed H. pylori positive by a diagnostic test. These patients randomly distributed into two groups and given treatment for 10 and 12 days respectively. UBT was used to find either H. pylori is eradicated or not. “Registry of clinical trials” registered this experiment. Results: For this research work, 196 patients were selected, after the concomitant therapy eradication rate was analyzed that comes out as 83 % (CI 95.0%: 76-90) and 88 % (CI 95%: 82-94) for 10 and 12 day therapy, respectively (p = 0.23). Then, prediction of per-protocol eradication was done and it came out as 85% (CI 95%: 79-92) and 92% (CI 95%: 87-97), respectively (p = 0.18). When side effects were compared between two groups, no statistical difference exist between two (3.5% vs. 8.0%; p = 0.419). Conclusion: All the results suggested that the concomitant therapy that was given for 12 days was more effective for treatment and per-protocol assessment. For the reduction of the cost of antibiotics, 12 day treatment is more effective for treatment as well as the replacement of 14 day treatment that was suggested by international rules.